Consequence study of pressurized CO2 release containing impurities with obstacles - Pham, H.H.P.L. (Trans Tech Publications Ltd, 2014)
A rupture or puncture of a carbon dioxide (CO2) pipeline results in a release of dense CO2 gas cloud mixed with toxic impurities such as hydrogen sulfide (H2S) to the ambient. This paper has proposed an approach for developing an accurate consequence model for CO2 release containing H2S in order to demonstrate a safe layout and other safeguards. Thus, a validated code using computational fluid dynamics (CFD) was applied to predict time-varying concentrations of CO2 and H2S at a point of downwind release area. Then overall fatality rate due to both CO2 and H2S has been estimated at this point. Results indicate that this is a suitable method for assessing the consequences of the release of CO2 via pipeline leakage. Â© 2014 Trans Tech Publications, Switzerland.